ADAPTABILITY OF VIETNAMESE SMEs TOWARD OUTSOURCING TREND - Tran, Nguyen T.H.; Van, Thong A; Truong, H.A. Tho; Trang, To Thuy; Thuy, Tran T.P. (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2015)
This article is to determine the adaptability of Vietnamese SMEs (small and toward international outsourcing trend.Â Organizations in developed countries usually find some less developed countries within which they may outsourceoperations. Outsourcing has become an effective good way for companies to increase profits by reducing productionÂ costs. This is attractive to less developed and developing countries as it encourages economic growth. However, toÂ become an attractive destination of outsourcers, these developing countries need to possess high level human resources,Â attractive policies and business climate in conjunction with excellent infrastructure but low operation costs. VietnameseÂ SMEs only focus on labor-based outsourcing services which can bring about much lower benefits than aknowledge basedÂ services. A survey was done to get the viewpoints of Vietnamese SMEsâ managers about outsourcing requirements.Â After that we use the zero-sum method to determine which factors Vietnamese SMEsâ managers think the outsourcersÂ should consider the most important when seeking outsource destination. Beside, we also base on background knowledgeÂ to understand Vietnamese SMEsâ entrepreneurship basing on this aspect. The result shows that Vietnamese SMEsÂ think costs, especially labor costs, operation costs and administration costs are most important elements encourageÂ outsourcers choose an outsourcing place.